The theory of integrated empowerment in the transition to adulthood: concepts and measures - Mouchrek, Najla; Benson, Mark (Frontiers in Sociology, 2023)
Introduction Developmental challenges in the transition to adulthood require a process of empowerment that enables young people to guide themselves and build capacities for adult commitments and roles. To examine this systemic process, we conducted an interdisciplinary investigation of constructs from prior literatures that relate to empowerment. Two foundational dimensions of empowerment emerged in relation to individual functioning and relational environments. Theoretical model The two dimensions are self-direction and meaningful roles in society. A creative process of theory construction informed by related literatures identified four component catalysts that drive these dimensions of empowerment among early adults: personal agency, sense of purpose, mentoring experience, and engagement in community. As developed in this article, the Integrated Empowerment Theory explains the relationships among these catalysts within the ongoing, multilayered process of empowerment in the transition to adulthood. A graphic representation in the article specifies the relationships among these theoretical concepts. Method and results To advance future research based on these theoretical concepts, we constructed multi-item measures of the four catalysts drawn from indicators in the empirical literature. The resulting scales were presented to participants in an empirical test of their technical adequacies. Participants were 255 early adult college students from eight colleges at a public land-grant research university in the United States. The 18-item scale includes four subscales: agency, purpose, mentoring, and community. The study findings evidenced robust internal consistency estimates across the scales (0.79–0.96). Discussion The Integrated Empowerment Theory and the corresponding scales provide tools for research to understand and promote positive developmental outcomes for youth as they navigate experimentation, life choices, and identity construction. The scales also imply a logical sequence for application and intervention. The sequence corresponds to four key catalysts: Community, Agency, Mentors, and Purpose, or CAMP. Although the conceptualization and the scales draw from a college population, the constructs have potential applicability, and await future research with additional age groups. For early adults, empowerment has particularly important implications for societal contributions. Creating contexts where youth can play meaningful roles in their emerging social world holds positive potential for society.